Adverse Events After MMR or MMRV Vaccine in Infants Under Nine Months Old. Issue 8 (August 2016) - Woo, Emily Jane; Winiecki, Scott K.; Arya, Deepa; Beeler, Judy
Abstract : Background: In the United States, measles is resurging, with more than 700 confirmed cases since January 2014. During measles outbreaks, vaccination as early as at 6 months of age is sometimes recommended for infants who are at risk for exposure. Methods: We searched the Vaccine Adverse Event Reporting System for reports of measles, mumps and rubella vaccine combined or measles, mumps, rubella and varicella vaccine combined vaccination in children less than 9 months of age. We performed a clinical assessment of each report and summarized the frequency, range, onset time and severity of adverse events. Results: After excluding 346 reports because they were duplicates or because they contained insufficient information about the child's age or vaccine(s), we retained 204 reports in the analysis, including 35 (17%) that were serious. Among the 169 nonserious reports, more than half (88; 52%) described a vaccination error without any adverse event per se. Other nonserious reports described fever, injection reactions and gastrointestinal symptoms. Serious adverse events included developmental disorders, fever and fussiness. There were 44 reports of fever, but only 4 cases began 5–12 days after immunization, the peak risk window. The vast majority of fever reports listed concomitant vaccines, such as diphtheria and tetanus toxoids, acellular or whole-cell pertussis vaccine. Conclusions: This review did not identify any major safety concerns. These findings may facilitate discussions about the risks and benefits of vaccinating infants who are potentially exposed to this life-threatening disease.